(untitled) (Medical Forum Monthly, 2024)
Objective: The objective of this study was to determine the frequency of early postoperative complications and mortality in patients undergoing colorectal cancer surgery and its relation with nutritional status. Study Design: Observational / descriptive study. Place and Duration of study: This study was conducted at the Indoor Department of General Surgery, Nishtar Hospital Multan from 02-01-2016 to 01-12-2016 Materials and Methods: In this study, Sixty patients of either gender with 30-60 year of age admitted for major colorectal cancer surgery with cancer stage of ≤ IIA were included in this study. We utilized hypoalbuminemia to recognize dietary status. All patients having resection of their rectum underwent mesorectal extraction, and patients with colorectal or coloanal anastomosis had a twofold stapled anastomosis. A SSI case was recognized utilizing CDC, USA definition, which expresses that "Wound would be viewed as surgical site infection if it happens inside 30 days of procedure and has any one of the accompanying: purulent discharge from the injury, agony or delicacy, restricted swelling, redness, malodor, fever". Results: Age range in this study was 30-60 years with mean age 48.500±5.37 years, mean BMI 28.116±1.84 Kg/m2 and mean duration of procedure was 3.066±0.60 hours. Majority of patients according to age groups were belongs to 46-60 years and there was more males than females. Majority of patients were belongs to stage I of cancer 39(65%) and hypoalbuminemia was seen in 58.3% patients. Twenty-one (35%) patients developed surgical site infection. Mortality was seen in 7 (11.7%) patients. SSI and mortality was significantly seen in patients of IIA cancer stage (p<0.05). Patients with hypoalbuminemia showed more frequency of SSI and mortality (p<0.05). Conclusion: Malnutrition is a more noticeable issue in colorectal cancer than other most basic cancer. Postoperative 30-day mortality and SSI were fundamentally connected with under nutrition in colorectal tumor.